Pengaruh Subsitusi Tepung Terigu dengan Umbi Gembili (Dioscorea esculenta L) Terhadap Sifat Kimia, Indeks Glikemik, dan Beban Glikemik Cookies - Dika Kartika Wardani (2022)
Obesity is a health problem whose prevalence continues to increase. Factors that influence obesity are eating foods high in energy and fat but low in fiber. Thus initiating the development of functional foods in an effort to maintain glycemic control to prevent obesity. The purpose of this study was to analyze the formulation of gembili tubers, nutritional content, glycemic index, glycemic load and organoleptic cookies substituted for wheat flour with gembili tubers. The method used in this study was Completely Randomized (CRD) with two designs and an in vivo method for testing the glycemic index. Data analysis used for nutritional content and glycemic index was One-way ANOVA then continued with Duncan's test, while organoleptic test used Kruskal-Wallis test and continued with Mann Whitney's test. The determination formula was selected using the exponential comparison method (MPE). The results of the analysis showed a significant difference in the proportion of wheat flour with gembili tubers on ash content, protein content, fiber, texture and cake taste (p<0.05). However, there was no significant difference in the proportion of wheat flour with water content, content, fat, carbohydrate content, glycemic index, glycemic load, color, and aroma of cookies (p>0.05). The cookies selected in this study were F4 (0% wheat flour: 100% gembili tubers). Further testing is needed to determine the shelf life and improve the cookie texture according to standards.